S178. International Federation of Clinical Neurophysiology (IFCN) guidelines for topographic and frequency analysis of resting state electroencephalographic rhythms. (May 2018) - Babiloni, Claudio
Abstract : Introduction: Resting state EEG (rsEEG) rhythms reflect neurophysiological mechanisms and operational functions related to the fluctuation of brain arousal and quiet vigilance in humans and are largely investigated in clinical practice and research in Clinical Neurophysiology. In 1999, the International Federation of Clinical Neurophysiology (IFCN) published the Guidelines entitled "IFCN Guidelines for Topographic and Frequency Analysis of EEGs and EPs" (Nuwer et al., 1999). In 2017, the IFCN Executive Committee committed to a Working Group of 15 field experts of four continents (Prof./Dr. Babiloni C., Barry R., Basar E., Blinowska K., Cichocki A., Drinkenburg W., Klimesch W., Knight R., Jeong J., Lopes da Silva F., Nunez P., Oostenveld R., Pascual-Marqui R., Valdes Sosa P., and Hallett M.) the update of the part of those Guidelines concerning frequency and topographic analyses of rsEEG rhythms. This contribution will report the outcome of the mentioned Working Group (That outcome is expected to be published in Clinical Neurophysiology in 2018 after a regular peer-review process). Methods: Recommendations about relevant procedures of recording, storage, visualization, and quantitative frequency and topographic analyses of rsEEG data in Clinical Neurophysiology of vigilance were expressed based on theoretical ground and relevant core literature findings. Those recommendations reflected the consensus in the Working Group. Results: Recommendations regarded main controversies in the field such as (1) the optimal experimental conditions ensuring that recordings of rsEEG rhythms fit requirements of a neurophysiological experiment on vigilance; (2) the minimum requirements of scalp electrode montage, reference electrode, and settings for subsequent frequency and topographical analyses; (3) choice of frequency bands; (4) linear/nonlinear synchronization and interdependence of rsEEG rhythms at scalp electrodes and sources; and (5) statistical modeling and neurophysiological inferences in clinical practice and research. Conclusion: Linear frequency and topographical source analyses of rsEEG rhythms (e.g., 10–20 electrode montage at minimum and extracephalic reference) are mature for both clinical practice and research applications. Nonlinear frequency and connectivity analyses of those rhythms require more research before their current use in clinical practice.